Role of laparoscopic techniques in the treatment of female genital pathology - Šuškić, Amer; Halilović Šuškić, Sanela; Oprić, Dejan; Maksimović, Siniša (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Laparoscopy or endoscopically examining the peritoneal cavity was first attempted in 1901 by George Kelling who called this examining procedure celioscopy. Laparoscopy provides direct visual access to inner pelvic anatomy without a major abdominal surgery so that anatomy of uterus, ovaries, and fallopian tubes can be studied in more details and abnormalities can be treated at the same time. Methods: This was a retrospective study which presents the results of laparoscopic treatment of various gynecological diseases in Cantonal hospital Travnik, Bosnia and Herzegovina in the period from 2003 to 2016. Total 295 cases were enrolled. All underwent laparoscopic surgery in general anesthesia. The results were statistically analyzed. Results: The total number of patients is 295. The incidence is highest in the age 20-49 with a peak of 30-39 years (41.35%). Ovarian cysts are most common pathological condition in 43.60%, Infertility in 16.39% and Ectopic pregnancy in 12.13%. The most commonly treatment was cystectomy 40.06%, then chromopertubation with ovarian drilling 18:29% in infertility, and adnexectomy 10.72%. Conclusions: Laparoscopy involves a minimal damage to body tissues. It is safer than open surgery. Laparoscopic treatment has contributed to faster treatment, faster recovery and reducing the cost of treatment, and thus raise the level of efficiency.